PDCT-07. EARLY RESULTS OF THE EMULATE THERAPEUTICS HÆLO™ SYSTEM IN PEDIATRIC BRAIN TUMORS. (11th November 2019) - Chang, Andrew; Gardner, Sharon; Jaboin, Jerry; Leary, Sarah; Loret De Mola, Rebecca; McClay, Edward; Morgan Murray, Donna; Nazemi, Kellie; Pai Panandiker, Atmaram; Salacz, Michael; Stapleton, Stacie; Kesari, Santosh; et al.
Abstract: BACKGROUND: The EMulate Therapeutics Hælo system is an investigational non-sterile, non-invasive, non-thermal, non-ionizing, portable, home-use medical device that uses a specific, localized ultra-low radio frequency energy ( ul RFE ® ) cognate for the treatment of pediatric brain tumors. METHODS: Sixteen patients with brain tumors consisting of diffuse midline glioma/diffuse intrinsic pontine glioma (DMG/DIPG, n=14), recurrent medulloblastoma (n=1), or anaplastic astrocytoma (n=1) – were treated with the Hælo under FDA's single-patient compassionate use pathway, as protocol deviations in a glioblastoma trial, or under TGA's Special Access Scheme. Baseline information and on-treatment safety and exposure data were collected. RESULTS: Patients ranged in age from 4 to 28 years (median = 8 years) and were diagnosed 91 – 1399 days (median = 397 days) prior to treatment with the Hælo system. Patients were treated for 2 – 52 weeks (median = 15 weeks), with 4 patients still alive (all with a diagnosis of DMG/DIPG), and 3 still on treatment (ranging 18 – 52 weeks). Two out of the 16 patients reported mild-moderate adverse events - one patient reported nausea, fatigue, and excessive sleepiness, and one patient reported vomiting. No device-related serious adverse events were reported. Other adverse events reported were generally associated with progressive disease. Unsolicited, anecdotal reports from some parents/caregivers noted improvements in mobility, speech, and visual acuity while on treatment. CONCLUSIONS: The Hælo system appears to be safe and feasible for the treatment of pediatric brain tumors. Given that therapy is delivered non-invasively and no device-related serious adverse events were reported, further prospective study of the investigational device is warranted.